2022
DOI: 10.3390/molecules27072279
|View full text |Cite
|
Sign up to set email alerts
|

Red Horse Chestnut and Horse Chestnut Flowers and Leaves: A Potential and Powerful Source of Polyphenols with High Antioxidant Capacity

Abstract: Aesculus flowers and leaves are an excellent source of bioactive compounds, including flavanols, phenolic acids, and anthocyanins, and the leaves also contain antioxidant carotenoids and chlorophylls. The aim of this study was to analyse and compare the amounts of bioactive compounds present in Aesculus hippocastanum and Aesculus × carnea flowers and leaves over two years. These two species from six independent locations (parks and green areas) located in Warsaw were assessed in this study. The dry matter by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Double-pigmented pansy flowers contained significantly more caffeic and p -coumaric acids than single-pigmented yellow pansy flowers ( Table 2 a). Bristly locust and red horse-chestnut flowers with dark (pink) petal colors were characterized by higher contents of phenolic acids such as caffeic acid, gallic acid, or chlorogenic acid compared to those with white flowers (black locust and horse chestnut) [ 55 , 64 ]. In the case of violet/yellow pansy flowers, we observed a significant interaction of experimental factors only in p -coumaric acid concertation.…”
Section: Resultsmentioning
confidence: 99%
“…Double-pigmented pansy flowers contained significantly more caffeic and p -coumaric acids than single-pigmented yellow pansy flowers ( Table 2 a). Bristly locust and red horse-chestnut flowers with dark (pink) petal colors were characterized by higher contents of phenolic acids such as caffeic acid, gallic acid, or chlorogenic acid compared to those with white flowers (black locust and horse chestnut) [ 55 , 64 ]. In the case of violet/yellow pansy flowers, we observed a significant interaction of experimental factors only in p -coumaric acid concertation.…”
Section: Resultsmentioning
confidence: 99%
“…It has been established that escin primarily accounts for the effectiveness of horse chestnut seed extract in decreasing edema and inflammation. 31 Coveted Pharmacological Properties of Horse Chestnut Extracts According to numerous scientific investigations, A. hippocastanum has major antioxidant, [32][33][34] antiinflammatory, [35][36][37] and anti-edematous 38 properties. The escin acts as an antioxidant via inhibiting hyaluronidase enzyme, but Wilkinson and brown state that this is insufficient to explain the potent venotonic effects of horse chestnut extract on the microvasculature.…”
Section: Important Chemical Constituents Of Horse Chestnut Seed Extractmentioning
confidence: 99%
“…43 The antioxidant proanthocyanidin A2 can be found in the triterpene saponin of escin. 35,[44][45][46] It has been demonstrated that the proteoglycan breakdown enzyme hyaluronidase is inhibited by escin. 47 In animal studies, it was discovered that increased release of prostaglandin F2 in the outer wall of veins inhibited the vasodilator effects of serotonin (5-hydroxytryptamine) and histamine.…”
Section: Protection Against Capillary Hyperpermeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Extracts and concentrates are used in the manufacture of creams and ointments with antiinflammatory properties to treat phlebitis and different kinds of cancer. However, culinary properties of horse chestnut flowers have been reported as well (Bielarska et al 2022).…”
Section: Introductionmentioning
confidence: 99%